Education for Husbands about Successful Breastfeeding (A Literatur Review) - Rogayah, Rogayah; Al-Bahra, Al-Bahra (STIKes RSPAD RSPAD Gatot Soebroto, 2023)
WHO has recommended mothers to breastfeed their babies until at least six months after birth. The success of this WHO recommendation depends on several factors, and one of these factors is husband's support. From the three journal articles reviewed in this research, husband's support was proven to be very supportive of the success of early initiation of breastfeeding and exclusive breastfeeding. With the husband's support and the husband's presence when breastfeeding mothers are still active to provide breast milk to their babies, premature cessation of breastfeeding can be prevented because breastfeeding mothers feel appreciated for their efforts so far in conceiving, giving birth and breastfeeding their babies. Therefore, husband's support is considered a very significant intervention for successful breastfeeding.